Subcutaneous IgG Replacement Therapy by Push in 32 Patients with Primary Immunodeficiency Diseases in Argentine - Bezrodnik, Liliana (2014)
Introduction: Regular replacement with immunoglobulin infusions is the mainstay of treatment in the majority of primary immunodeficiencies. Several studies showed that Subcutaneous Immunoglobulin (SCIG) has similar efficacy to Intravenous Immunoglobulin (IVIG) in preventing infections in PID patients. Here we report effectiveness, safety and tolerance of SCIG replacement therapy by push in 32 pediatric and adult patients with humoral PID in Argentina. Results: We describe 32 patients that received SCIG treatment between July 2011 and May 2012. 17 male and 15 female from 2 Immunology Centers; aged from 8 months to 40 years (median: 11 years). 30 patients previously received IVIG treatment. Among them, fifteen received 9 months of SCIG treatment administered by pump. The other 2 patients started the immunoglobulin replacement treatment directly with SCIG by push. The mean dose of SCIG was 133 mg/kg/week (range 100-192). The annual rate of any infection was 1, 2 infection/year/patient for subcutaneous treatment. The frequency of adverse effects was 0.02% with the SCIG. At the end of the study, all patients chose SCIG home-therapy regimen and referred much more comfort with SCIG by push. Conclusion: Self-administered subcutaneous immunoglobulin therapy by push is an effective and safe alternative therapy for patients with PID.